Comparison of the complications between minimally invasive surgery and open surgical treatments for early-stage cervical cancer: A systematic review and meta-analysis. - Yilin Li (Public Library of Science (PLoS), 2021)
Background This meta-analysis comprehensively compared intraoperative and postoperative complications between minimally invasive surgery (MIS) and laparotomy in the management of cervical cancer. Even though the advantages of laparotomy over MIS in disease-free survival and overall survival for management of gynecological diseases have been cited in the literature, there is a lack of substantial evidence of the advantage of one surgical modality over another, and it is uncertain whether MIS is justifiable in terms of safety and efficacy. Methods In this meta-analysis, the studies were abstracted that the outcomes of complications to compare MIS (laparoscopic or robot-assisted) and open radical hysterectomy in patients with early-stage (International Federation of Gynecology and Obstetrics classification stage IA1-IIB) cervical cancer. The primary outcomes were intraoperative overall complications, as well as postoperative aggregate complications. Secondary outcomes included the individual complications. Two investigators independently performed the screening and data extraction. All articles that met the eligibility criteria were included in this meta-analysis. Results The meta-analysis finally included 39 non-randomized studies and 1 randomized controlled trial (8 studies were conducted on robotic radical hysterectomy (RRH) vs open radical hysterectomy (ORH), 27 studies were conducted on laparoscopic radical hysterectomy (LRH) vs ORH, and 5 studies were conducted on all three approaches). Pooled analyses showed that MIS was associated with higher risk of intraoperative overall complications (OR = 1.41, 95% CI = 1.07-1.86, P<0.05) in comparison with ORH. However, compared to ORH, MIS was associated with significantly lower risk of postoperative aggregate complications (OR = 0.40, 95% CI = 0.34-0.48, P = 0.0143). In terms of individual complications, MIS appeared to have a positive effect in decreasing the complications of transfusion, wound infection, pelvic infection and abscess, lymphedema, intestinal obstruction, pulmonary embolism, deep vein thrombosis, and urinary tract infection. Furthermore, MIS had a negative effect in increasing the complications of cystotomy, bowel injury, subcutaneous emphysema, and fistula. Conclusions Our meta-analysis demonstrates that MIS is superior to laparotomy, with fewer postoperative overall complications (wound infection, pelvic infection and abscess, lymphedema, intestinal obstruction, pulmonary embolism, and urinary tract infection). However, MIS is associated with a higher risk of intraoperative aggregate complications (cystotomy, bowel injury, and subcutaneous emphysema) and postoperative fistula complications.